GOOD FAITH IN CONTRACT LAW: THE MALAYSIAN PERSPECTIVE - NG SENG YI, (Journal of Malaysian and Comparative Law, 2025)
The recognition of a general duty of good faith in contracts varies by country. In Malaysia, it has become the subject matter of recent cases but without much academic writing. This article seeks to complement the existing legal literature and to generate discussion on this area of law. This article uses a doctrinal approach with comparative law analysis to examine the duty of good faith in contract law. Like England and Singapore, Malaysia does not recognise a general duty of good faith in contracts. However, it has developed the law on a piecemeal basis through contractual implied terms. This approach is pragmatic for two reasons: first, it acknowledges that good faith is already inherent in Malaysian contract law; second, context is crucial- a duty of good faith will only be implied by law and/or in fact into contracts when the tests of implied terms are satisfied. This approach is more likely to respect the intention of the parties than having a general overriding duty of good faith since it affirms the freedom of contract. This article further highlights the potential challenges arising from the introduction of ‘relational’ contracts as to whether a general duty of good faith can be implied in such contracts. It is argued that if the parties intend to impose a duty of good faith, they should expressly stipulate it in the contract for the avoidance of doubt.